2014
DOI: 10.1038/nrgastro.2014.10
|View full text |Cite
|
Sign up to set email alerts
|

HCC therapies—lessons learned

Abstract: The antiangiogenic multikinase inhibitor sorafenib was the first systemic agent to demonstrate a significant improvement in the overall survival of patients with advanced hepatocellular carcinoma (HCC), thereby introducing molecularly-targeted therapy in a therapeutic field of unmet needs. However, survival benefits for patients on sorafenib treatment are modest in clinical practice and advancing the field is far more challenging than initially anticipated. Molecular and clinical heterogeneity diminishes signa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
124
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(125 citation statements)
references
References 37 publications
1
124
0
Order By: Relevance
“…Preclinical, clinical, and comparison studies in humans using a DNA plasmid containing H19 regulatory sequences that drive the expression of an intracellular toxin (diphtheria toxin A-fragment) have demonstrated promising results in several types of carcinoma. 27 Further, our preclinical study in a murine model also indicated that stable overexpression of H19 promotes tumor formation of glioblastoma cells and induces tumor cell proliferation and angiogenesis in vivo. Therefore, we believe that H19 plays an important role in tumorigenicity and stemness of glioblastoma cells and thus may represent a therapeutic target for treatment of glioblastoma in the future.…”
Section: Discussionmentioning
confidence: 88%
“…Preclinical, clinical, and comparison studies in humans using a DNA plasmid containing H19 regulatory sequences that drive the expression of an intracellular toxin (diphtheria toxin A-fragment) have demonstrated promising results in several types of carcinoma. 27 Further, our preclinical study in a murine model also indicated that stable overexpression of H19 promotes tumor formation of glioblastoma cells and induces tumor cell proliferation and angiogenesis in vivo. Therefore, we believe that H19 plays an important role in tumorigenicity and stemness of glioblastoma cells and thus may represent a therapeutic target for treatment of glioblastoma in the future.…”
Section: Discussionmentioning
confidence: 88%
“…Hepatocellular carcinoma (HCC) is a complex and heterogeneous tumor type with multiple genetic and epigenetic alterations ( 1 ). Sorafenib, standard of care for patients with advanced HCC in many countries, slows the growth of advanced liver cancers and increases patient survival by an average of 3 months ( 2,3 ).…”
Section: Introductionmentioning
confidence: 99%
“…Especially in heterotopic model systems these are often artificially high (e.g., subcutaneous tumor implants). Second, a compromised liver function presents a major obstacle in clinical therapy trials, which are often jeopardized by increased drug toxicity (28).…”
Section: Liver Damagementioning
confidence: 99%